SURVIVAL TREE SCORE: A NOVEL APPROACH TO PREDICT MORTALITY IN CIRRHOTIC PATIENTS - BASTO, Samanta Teixeira; NASCIMENTO, Emília Matos do; PEREIRA, Basilio de Bragança; RIBEIRO FILHO, Joaquim; PEREZ, Renata de Mello; NOGUEIRA, Cristiane Alves Villela (Brazilian Journal of Biometrics, 2020)
Although Model for End-Stage Liver Disease (MELD) score is adopted worldwide for liver transplant allocation, but it has prognostic limitations. The aim of this study was to apply the survival tree analysis to evaluate interaction between variables related to mortality in cirrhotics patients enlisted for liver transplantation, and to develop a new mortality predictive score. Demographic, clinical and laboratory data of cirrhotic patients waiting for liver transplantation during a 12-year period were considered. Charts from 765 patients were reviewed. The interaction between prognostic covariates was obtained using a survival tree analysis. In order to develop the predictive score, Cox regression analysis was performed applying significant data obtained by the survival tree analysis. The prognostic covariates evaluated in the survival tree were MELD score, Child-Pugh score, serum sodium, viral disease etiology, hepatocellular carcinoma diagnosis and generated a coefficient for each. Based on the survival tree analysis, MELD = 15 was the primary root variable (p<0.001). The survival tree provided eight prognostic groups. The higher mortality hazard ratio (HR) risk was observed in the MELD >28 group (HR= 16.7). The new score (Survival Tree Score – STS) was obtained according to the coefficients provided. The STS prognostic performance was superior to MELD score (AUROC 0.713 vs 0.653, p<0.001). STS, could be a useful tool to accurately identify individual mortality risk in advanced liver disease.